Pengawasan DPRD Provinsi Gorontalo Terhadap Penerapan Peraturan Daerah Tahun 2020 (Jurnal Begawan Hukum (JBH), 2024)
This research aims to find out how supervision is carried out by the Regional Representative Council of Gorontalo Province regarding the implementation of regional regulations promulgated in 2020. This type of research is Empirical Research. The research results show that the forms of supervision over regional regulations are divided into two, namely preventive supervision and repressive supervision. Preventive supervision is carried out before a regional regulation is passed. Repressive supervision is carried out after the regional regulation is passed, where what is supervised is the implementation of the regional regulation and is carried out by the Provincial Regional People's Representative Council. Repressive supervision in the implementation of regional regulations in Gorontalo Province is carried out by the Regional People's Representative Council in two ways: first, going directly to the field to directly observe the implementation of regional regulations; and secondly, hold an evaluation meeting on the implementation of the regional regulations by inviting agencies related to the regional regulations being supervised.